2023
DOI: 10.1021/acs.inorgchem.3c02398
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Semiconducting Behavior of Magnesium Polysulfides by Nonequivalent sp3 Hybridizations

Guang Zhang,
Kai Wang,
Qiaoyu Liu
et al.

Abstract: The Mg/S battery has attracted enormous interest in recent years due to its high theoretical capacity, low cost, and high security. However, the understanding of many intermediate magnesium polysulfides in the Mg/S battery remains elusive. Combining extensive structural search and first-principles calculations, we investigate the phase stability, structural character, and electronic structure of magnesium polysulfides in a wide range from MgS to MgS8. The pyrite-type MgS2 (space group: Pa3̅) is predicted to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Notably, the tetrahedral sp 3 nonequivalent hybridization state possesses higher energy and better coupling capacity, accompanied by stronger antibonding states (σ*), resulting in stronger bonds between Mg and O. In turn, this strengthened the binding force between Mg-CUS and phosphate (Figure h) . Our findings indicated that MOFs presented a more stable reaction system, and the reaction was more spontaneous, thus reducing the molecular adsorption energy.…”
Section: Resultsmentioning
confidence: 77%
“…Notably, the tetrahedral sp 3 nonequivalent hybridization state possesses higher energy and better coupling capacity, accompanied by stronger antibonding states (σ*), resulting in stronger bonds between Mg and O. In turn, this strengthened the binding force between Mg-CUS and phosphate (Figure h) . Our findings indicated that MOFs presented a more stable reaction system, and the reaction was more spontaneous, thus reducing the molecular adsorption energy.…”
Section: Resultsmentioning
confidence: 77%